Conditional Survival-Based "Abbreviated" Routine Cancer Surveillance for Pathologic Stage IB Melanoma. Issue 11 (November 2017) - Kukar, Moshim; Gabriel, Emmanuel; May, Rebecca; Cho, Edward; Lichtenthal, Michelle; Groman, Adrienne; Skitzki, Joseph; Francescutti, Valerie; Kane, John M.
A negative sentinel lymph node biopsy (SLNB) for stage IB (T1b/T2a N0) melanoma would predict an excellent long-term prognosis. Combined with the concept of conditional survival, an "abbreviated" cancer surveillance strategy was implemented to reduce the number of visits and total length of follow-up. Retrospective review of all pathologic stage IB melanoma patients (negative SLNB) at a single institution between 2006 and 2008 after implementation of an "abbreviated" cancer surveillance; clinic visits every six months for five years followed by one annual visit (total follow-up six years). Patient demographics, tumor characteristics, and information regarding recurrences were obtained. Recurrence-free, disease-specific, and overall survival were calculated. Eighty-seven patients underwent the "abbreviated" cancer surveillance. Median age was 55.4 years and 50.6 per cent were male. Median Breslow thickness was 1.1 mm (range 0.5–2.0 mm) and 1.1 per cent were ulcerated. Primary tumor site was 49 per cent extremities, 39 per cent trunk, and 12 per cent head/ neck. Median follow-up was 68.6 months. Five-year recurrence-free, disease-specific, and overall survivals were 89, 95, and 88 per cent, respectively. During surveillance, 10 patients had concerning symptoms or physical findings prompting subsequent workup, all of which were negative for recurrence/metastases. There were only three true melanoma recurrences; all were distant metastases and presented symptomatically between scheduled follow-up visits. In light of the excellent prognosis for pathologic (SLNB negative) stage IB melanoma, an "abbreviated" cancer surveillance schedule based on conditional survival would reduce both direct and indirect costs in this cohort. The few recurrences were symptomatic and unlikely to have changed with more intensive surveillance.